Numerical study of the horizontal shading devices effect on the thermal performance of promotional apartments: Case of El-Alia-Biskra - Berkouk, Djihed; Mazouz, Said (Journal of Applied Engineering Science & Technology, 2017)
The aim of this research is to evaluate the impact of horizontal shading devices on the thermal performance of promotional apartments in the city of Biskra. In this regard, various sizes of horizontal shading devices which allow making an adequate choice were proposed to guarantee the best thermal comfort level for this apartment type. The simulations were performed by using the TRNSYS© software to estimate objectively the indoor thermal comfort of studied apartments. The comparative analysis between the simulation results of the existing apartments and the shading scenarios shows that the promotional apartments appear to be unsuited to the desert climate and the analysis shows the effectiveness of the horizontal shading devices on the thermal performance of the space by reducing the indoor air temperature during the summer period.